The PE/PPE family proteins of Mycobacterium tuberculosis: evolution, function, and prospects for tuberculosis control - Zhijing Zhang; Zhijing Zhang; Le Dong; Xin Li; Taibing Deng; Qinglan Wang (Frontiers in Immunology)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a leading global health threat, exacerbated by drug resistance and inadequate vaccine efficacy. The PE/PPE protein family, unique to mycobacteria, constitutes ~10% of the Mtb genome and plays critical roles in bacterial physiology, immune evasion, and host-pathogen interactions. This review synthesizes advances in understanding the evolutionary expansion, structural diversity, and functional versatility of PE/PPE proteins, emphasizing their co-evolution with type VII secretion systems (T7SS). We highlight their roles in nutrient acquisition, immune modulation, and pathogenesis, alongside their potential as diagnostic and vaccine targets. Clinical progress in PE/PPE-based vaccines, such as M72/AS01E and ID93/GLA-SE, underscores their promise in combating TB, while challenges in epitope variability and functional redundancy demand innovative strategies. By integrating evolutionary, structural, and immunological insights, this review provides a roadmap for leveraging PE/PPE biology to develop next-generation TB interventions.